Differential binding of bispyridinium oxime drugs with acetylcholinesterase - Kesharwani Manoj K; Ganguly Bishwajit; Das Amit; Bandyopadhyay Tusar (Acta Pharmacologica Sinica; Vol 31, No 3 (March 2010): Acta Pharmacologica Sinica, 2016)
Aim: To performe a time-dependent topographical delineation of protein-drug interactions to gain molecular insight into the supremacy of Ortho-7 over HI-6 in reactivating tabun-conjugated mouse acetylcholinesterase (mAChE). Methods: We conducted all-atom steered molecular dynamics simulations of the two protein-drug complexes. Through a host of protein-drug interaction parameters (rupture force profiles, hydrogen bonds, water bridges, hydrophobic interactions), geometrical, and orientation ordering of the drugs, we monitored the enzyme's response during the release of the drugs from its active-site. Results: The results show the preferential binding of the drugs with the enzyme. The pyridinium ring of HI-6 shows excellent complementary binding with the peripheral anionic site, whereas one of two identical pyridinium rings of Ortho-7 has excellent binding compatibility in the enzyme active-site where it can orchestrate the reactivation process. We found that the active pyridinium ring of HI-6 undergoes a complete turn along the active site axis, directed away from the active-site region during the course of the simulation. Conclusion: Due to excellent cooperative binding of Ortho-7, as rendered by several cation-π interactions with the active-site gorge of the enzyme, Ortho-7 may be a more efficient reactivator than HI-6. Our work supports the growing body of evidence that the efficacy of the drugs is due to the differential bindings of the oximes with AChE and can aid to the rational design of oxime drugs.